Fruit Pest Control for Home Gardens - Kadir, Sorkel; Bauernfeind, Robert J.; Upham, Ward (My University, 2006)
This publication is for home gardeners who plant fruit trees, brambles, grapes, or strawberries. These gardeners would like to produce fruits without pests or disease.
C592_2006_01
Keywords: C592; Lawn and Garden; Insects; C